The Role of Zakat in Poverty Alleviation: A Socio-Economic Analysis - Muhammad Aiman; Munkhotilah Rifki Nurhidayat (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2025)
Introduction to The Problem: Poverty continues to be a major issue in Muslim-majority countries across Southeast Asia, the Middle East, and Africa. Despite government programs, inequality and wealth distribution gaps are still increasing. Zakat offers a structured mechanism for redistribution, but its implementation is often limited by weak governance, low public awareness, and poor integration into national development frameworks. Purpose/Objective Study: This study aims to analyze the role of zakat in poverty alleviation from a socio-economic perspective. It seeks to identify zakat’s contribution to reducing poverty, assess the effectiveness of management and distribution, examine institutional challenges, and provide recommendations to strengthen the zakat system for greater social welfare impact. Design/Methodology/Approach: The study adopts a qualitative approach using a literature review of academic journals, Islamic economics books, institutional zakat reports, and empirical research. Previous findings are compared across local, national, and international contexts to understand patterns, weaknesses, and opportunities in zakat management. Findings: The findings show that zakat significantly reduces poverty when managed transparently and professionally. Zakat supports mustahik by meeting basic needs and funding empowerment programs such as business capital assistance, skills training, and scholarships. Digital zakat platforms enhance collection and distribution efficiency, but obstacles remain, including regulatory inconsistencies, low muzakki participation, and weak long-term planning.